Looking up: regional patterning in the fly eye. - D'Costa, A.; Moses, K. (Developmental Cell, 2003)
The Drosophila compound eye includes a dorsal domain specialized for the detection of the plane of polarized light. Two new papers show that this domain is controlled by graded Wingless signals acting through the homeodomain transcription factor Homothorax.